A novel electrochemical aptasensor based on MWCNTs–BMIMPF6 and amino functionalized graphene nanocomposite films for determination of kanamycin. Issue 13 (11th May 2015) - Qin, Xiaoli; Guo, Wenjuan; Yu, Huijing; Zhao, Juan; Pei, Meishan
Abstract : A simple and cost-efficient electrochemical aptasensor for sensitive and specific detection of kanamycin was reported. Abstract : A simple electrochemical sensor based on a novel composite film consisting of multi-walled carbon nanotubes (MWCNTs), a room temperature ionic liquid (RTIL) of 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF6 ), and amino functionalized graphene (GR–CO–NH–CH2 –CH2 –NH2 ) was constructed for the detection of kanamycin. Firstly, MWCNTs–BMIMPF6 composites were fabricated on the surface of a glass carbon electrode (GCE). The synergy mechanism between the MWCNTs and RTIL has been discussed. Secondly, GR–CO–NH–CH2 –CH2 –NH2 was modified on the first film, which could greatly improve the conductivity of the electrode. The structure of the resultant graphene oxide (GO) was confirmed by FTIR and SEM. The properties of the aptasensor were characterized by electrochemical methods. Under the optimum conditions, the electrochemical aptasensor exhibited a wide linear range for kanamycin from 0.001 to 100 μM with a low limit of detection of 0.87 nM (S/N = 3). The as-prepared aptasensor showed high sensitivity, reproducibility and stability. Finally, the proposed electrochemical aptasensor was successfully applied for the detection of kanamycin in a real sample.